Biocompatible Yb3+/Er3+ Co-activated La-2 (WO4)(3) Upconversion Nanophosphors for Optical Thermometry, Biofluorescent, and Anticancer Agents - Kumar, K. Naveen; Kang, Gumin; Lim, Jiseok; Choi, Jungwook (American Chemical Society, 2022)
Non-cytotoxic upconversion nanocrystals are preferred candidates because they offer exceptional advantages for numerous applications, ranging from optical thermometry to bioimaging/biomedical applications. In this report, we demonstrate the luminescence characteristics and practical utility of a multifunctional upconversion nanophosphor based on Yb3+/Er3+:La-2(WO4)(3) (LWO) flakes. Strong upconversion green emission was observed from 6-mol % Er3+-doped LWO nanophosphor flakes excited by a 980 nm laser. We further enhanced the upconversion emission considerably by co-doping LWO nanophosphors with Yb3+ /Er3+ to exploit energy migration from Yb3+ to Er3+ ions. The exceptional improvement in upconversion green and near-infrared emission was achieved by Yb3+ ion co-doping up to 6 mol %; beyond 6 mol %, emission intensities remarkably dropped due to concentration quenching. Photometric parameters were evaluated with and without Yb3+ ion-doped LWO nanophosphors, which exhibited a high green color purity of 95.6%, to elucidate their energy transfer mechanism. In addition, temperature-dependent upconversion emission trends were evaluated by analyzing the fluorescence intensity ratio, exhibiting higher temperature sensitivity than that previously reported. This suggests the applicability of our proposed nanophosphors to optical thermometry. As for bioimaging applications, the non-cytotoxicity of the optimized nanophosphor was confirmed based on distinct fluorescence images of a normal fibroblast cell line (L929). Furthermore, we demonstrated the strong cytotoxicity of nanophosphors against human colon cancer (HCT-116) cells. Based on the results, non-cytotoxic Yb3+(6 mol %)/Er3+ (6 mol %):LWO upconversion nanophosphor flakes are expected to be exceptional candidates owing to their extensive suitability to the fields of upconversion lasers, optical thermometry, and biomedical and anticancer applications. The results indicate the potential of upconversion materials in the effective execution of multiple strategic applications.